Fanconi anemia pathway - Rodríguez, Alfredo; D'Andrea, Alan (Current biology, 2017)
Rodríguez and D'Andrea introduce the Fanconi anemia pathway and its role in DNA repair and other cellular functions.Rodríguez and D'Andrea introduce the Fanconi anemia pathway and its role in DNA repair and other cellular functions.